Pre‐hospital emergency anaesthesia in trauma patients: An observational study from a state‐wide Australian pre‐hospital and retrieval service. (30th March 2022) - Maclure, Paul; Gluck, Samuel; Kerin, Kate; Boyle, Laura; Ellis, Daniel
Abstract: Objective: To assess the performance of an Australian pre‐hospital and retrieval medicine (PHRM) service against the National Institute for Health and Care Excellence (NICE) standard which recommends that pre‐hospital emergency anaesthesia (PHEA) in trauma patients should be conducted within 45‐min of first contact with emergency services. Methods: Retrospective observational study of all adult trauma patients in which PHEA was conducted by the PHRM service covering a 5‐year period from January 2015 to December 2019. Results: Over the 5‐year study period, 1509 (22%) of the PHRM service workload comprised primary retrievals from scene. Most 1346 (89%) of these cases had a primary diagnosis of trauma. Of these we have complete data for 328 of the 337 cases requiring a PHEA and 121 (37%) patients received this within the recommended 45‐min time frame. The service attended in rapid response vehicles ( n  = 160, 49%), rotary wing ( n  = 151, 46%) and fixed wing ( n  = 17, 5%) transport modalities. For a service covering 983 482 km 2, the median distance travelled to patients was 35 (16–71) km and the median time to PHEA was 54 (38–80) min. Conclusions: In a cohort of 337 patients treated by a dedicated PHRM service in South Australia, the median time to PHEA was 54 (38–80) min with only 37% of patients receiving PHEA within 45 min from the activation of the team. Despite differing patient demographics, the percentage of patients receiving PHEA within the recommended time frame was greater than a similar cohort from the UK. However, both data sets still fall short of recommended targets. Abstract : Compliance with the National Institute for Health and Care Excellence 45‐min to pre‐hospital emergency anaesthesia guideline – an Australian retrieval service.